Relevance of palatal rugae as a method of forensic identification - Barrera Silva, Almendra (2020)
Human identification is one of the primary objectives of forensic dentistry. To achieve this scientificidentification, dentists must find characteristics such as age, sex, and other individualizing dentaltraits. The oral cavity offers many possibilities for identification, not only based on teeth and thebones of the cranial cavity; but also on the oral soft tissues; thus, offering us a wider field of study.Rugoscopy, a technique based on the study of palatal rugae, is a little explored method ofidentification, but is of great utility in forensic dentistry. Palatal rugae are immutable and perennialstructures, which, are protected from external trauma due to their location in the oral cavityand are not altered with the vicinity of dental prostheses or by erosion of chemical substances.Since all human beings present different rugae Since rugae differ among all humans in termsof size, position, number, and arrangement (their shape does not change from birth to death),they are important elements in the identification process of people from whom fingerprints areunrecoverable. Therefore, the aim of this study was to review the usefulness of rugoscopic analysisas an effective and low-cost method for identifying living subjects, recent corpses, and mummifiedor ancient corpses.